Attention-Deficit Hyperactivity in Elementary School Children in Ulaanbaatar: Spectral Analysis of Electroencephalogram and Emotional Intelligence - Enkhtuya, Battamir; Bayarsaikhan, Amgalan (International Journal of Innovative Research in Medical Science, 2022)
The acronym of ADHD stands for Attention-deficit hyperactivity disorder; it is a disorder that occurs during childhood development which presents signs of reduced attention and hyperactivity/impulsivity. This study presented the direct association between emotional ability and spectral analysis of electroencephalography of Mongolian children with ADHD and healthy control groups. The sample consisted of 60 children (20 % female; M age = 9.34, SD = 0.96) attending primary schools in Ulaanbaatar, Mongolia. All in all, 60 children of both gender aged between 7-12 years old were included in the study. The control group consisted of 30 children matched with the case group by age, gender, and school year. The 30 ADHD cases were determined through clinical interviews from parents and teachers with Teachers and Parents' survey versions of DSM-IV (“Diagnostic and Statistical Manual of Mental Disorders”). After determining that the variables were normally distributed, the chi-square test was performed to determine significant differences in the distribution of the risk factor variables after expressing their incidence numbers in children with and without the diagnosis of ADHD. Results: “Interpersonal scales, adaptability scales, general mood scales, and total EQ scores were significantly lower statistically in the ADHD group, and positive emotional scale was comparable between the two groups (p = 0.163)”. The study found a statistically significant increase in the posterior absolute delta and theta power in all parts of the brain in the ADHD group concerning the healthy group. At the same time, there was a decrease in the absolute alpha band located at the posterior part of the brain and beta in all parts, and theta/beta, theta/alpha ratio was significantly increased in all parts of the brain.